Analisis Pengaruh Promosi Dan Harga Terhadap Peningkatan Penjualan Pada PT. Fuji Seat indonesia - Budi Rahman; Pandoyo; Neli Marita (Klak Klik Inovasi Digital, 2020)
This study aims to find out the simultaneous and partial influence of Promotion and Price on Sales Increase in PT. Fuji Seat Indonesia. The time used to conduct research and collect the necessary data is less than four months long starting from February to June 2012. The results of analysis and discussion in chapter 4 show that the promotion conducted by PT. Fuji Seat Indonesia statistically does not affect sales proven by a very significant increase in sales. Based on the conclusions that have been done, the advice to the company should be in improving the company's performance more focused on the promotion so that the products produced are better known by other companies outside the existing partners while maintaining good relations with existing partners.